Design and fabrication of magnetic shock absorber - Gopinath, S.; Golden Renjith, R.J.; Dineshkumar, J. (International Journal of Engineering and Technology, 2014)
In a vehicle, shock absorber reduces the effect of travelling over rough ground, without shock absorber the vehicle would have a bouncing ride, as an energy is stored in the spring and then released to the vehicle, possibly exceeding the allow range of suspension movement [1]. Control of excessive suspension movement without shock absorption requires stiffer springs, which would intern gives a harsh ride. Shock absorber allows the use of soft springs while controlling the rate of suspension movement in response to bumps [2]. In this project a new suspension system based on magnetic power which can be used in automobile in future. The suspension system consists of magnets freely moving inside the cylinder with their same poles facing each other. Since the magnetic poles repel each other while moving closer, the up and down spring action is obtained.